Asymmetric localization of DLC1 defines avian trunk neural crest polarity for directional delamination and migration. Issue 1 (December 2017) - Liu, Jessica; Rao, Yanxia; Cheung, May; Hui, Man-Ning; Wu, Ming-Hoi; Chan, Lo-Kong; Ng, Irene; Niu, Ben; Cheah, Kathryn; Sharma, Rakesh; Hodgson, Louis; Cheung, Martin
Abstract Following epithelial-mesenchymal transition, acquisition of avian trunk neural crest cell (NCC) polarity is prerequisite for directional delamination and migration, which in turn is essential for peripheral nervous system development. However, how this cell polarization is established and regulated remains unknown. Here we demonstrate that, using the RHOA biosensor in vivo and in vitro, the initiation of NCC polarization is accompanied by highly activated RHOA in the cytoplasm at the cell rear and its fluctuating activity at the front edge. This differential RHOA activity determines polarized NC morphology and motility, and is regulated by the asymmetrically localized RhoGAP Deleted in liver cancer (DLC1) in the cytoplasm at the cell front. Importantly, the association of DLC1 with NEDD9 is crucial for its asymmetric localization and differential RHOA activity. Moreover, NC specifiers, SOX9 and SOX10, regulateNEDD9 andDLC1 expression, respectively. These results present a SOX9/SOX10-NEDD9/DLC1-RHOA regulatory axis to govern NCC migratory polarization. Following epithelial-mesenchymal transition, avian trunk neural crest cell polarity determines directional migration but how this is established is unclear. Here, the authors find that the RhoGAP, Deleted in liver cancer 1, is asymmetrically localized in the cytoplasm, governing neural crest migratory polarization.